The Role of Book Features in Young Children's Transfer of Information from Picture Books to Real-World Contexts - Strouse, Gabrielle A.; Nyhout, Angela; Ganea, Patricia A. (Frontiers in Psychology, 2018)
Picture books are an important source of new language, concepts, and lessons for young children. A large body of research has documented the nature of parent-child interactions during shared book reading. A new body of research has begun to investigate the features of picture books that support children’s learning and transfer of that information to the real world. In this paper, we discuss how children’s symbolic development, analogical reasoning, and reasoning about fantasy may constrain their ability to take away content information from picture books. We then review the nascent body of findings that has focused on the impact of picture book features on children’s learning and transfer of words and letters, science concepts, problem solutions, and morals from picture books. In each domain of learning we discuss how children’s development may interact with book features to impact their learning. We conclude that children’s ability to learn and transfer content from picture books can be disrupted by some book features and research should directly examine the interaction between children’s developing abilities and book characteristics on children’s learning.